The Digital Literacy of The First Semester Students in Physics Education - Rahmat Rizal; Dadi Rusdiana; Wawan Setiawan; Parsaoran Siahaan (Jurnal Pendidikan Fisika, 2020)
Technology continuously facing the development requires a significant change for the community to master several competencies in using and utilizing various facilities in digital technology, including teachers as a component that plays a important role in education must be equipped with digital literacy. The purpose of this study was to obtain a digital literacy description of physics education students as preservice physics teacher in the first semester. This research was conducted using a descriptive method involving 80 first-semester physics education students at a university in Tasikmalaya. Data is collected by using tests and interviews. The instrument used was a valid and reliable digital literacy test as well as an interview guide. Data obtained is processed by determining the student score means and correlated with the results of the interview. The results showed that the mean of student’s digital literacy was 50 with a low category. Three digital literacy competency areas owned by students show that the mean literacy competency of information and digital data is 36 (low category), the mean of communication and collaboration competency is 68 (medium category), and the mean of digital content creation is 47 (low category).